2013
DOI: 10.1104/pp.112.212712
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Visualizations of Drought-Induced Embolism Spread in Vitis vinifera      

Abstract: Long-distance water transport through plant xylem is vulnerable to hydraulic dysfunction during periods of increased tension on the xylem sap, often coinciding with drought. While the effects of local and systemic embolism on plant water transport and physiology are well documented, the spatial patterns of embolism formation and spread are not well understood. Using a recently developed nondestructive diagnostic imaging tool, high-resolution x-ray computed tomography, we documented the dynamics of drought-indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
157
2
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(177 citation statements)
references
References 49 publications
17
157
2
1
Order By: Relevance
“…Although the AE activity may continue after the selected endpoint (Figure 3), the obtained P50 values (´2.30 to´2.73 MPa) corresponded well with values found in literature for grapevine (´2.17 tó 2.97 MPa; [82,83]), from which was concluded that the endpoint was accurate, and that the remaining AE activity was related to other sources than cavitation. Strong evidence for their approach was given by validation with X-ray micro-computed tomography (µCT), which showed quite similar patterns for both visually and acoustically detected cavitation [31] (Figure 4).…”
Section: Endpoint Selectionsupporting
confidence: 72%
“…Although the AE activity may continue after the selected endpoint (Figure 3), the obtained P50 values (´2.30 to´2.73 MPa) corresponded well with values found in literature for grapevine (´2.17 tó 2.97 MPa; [82,83]), from which was concluded that the endpoint was accurate, and that the remaining AE activity was related to other sources than cavitation. Strong evidence for their approach was given by validation with X-ray micro-computed tomography (µCT), which showed quite similar patterns for both visually and acoustically detected cavitation [31] (Figure 4).…”
Section: Endpoint Selectionsupporting
confidence: 72%
“…Vessel diameter (d) was derived by A ¼ pðd=2Þ 2 . Percentage theoretical loss of xylem hydraulic conductivity was determined using a modified Hagen-Poiseuille equation (Tyree and Ewers, 1991;Brodersen et al, 2013;Knipfer et al, 2015). The xylem hydraulic conductivity (k h ) of the population of embolized and water-filled vessels of the roots was calculated according to:…”
Section: Microct Image Analysismentioning
confidence: 99%
“…Using a semiautomated routine in Fiji (Schindelin et al, 2012; as described in Brodersen et al, 2013), vessel number and cross-sectional area (A) were determined by using the Analyze Particles tool. Vessel diameter (d) was derived by A ¼ pðd=2Þ 2 .…”
Section: Microct Image Analysismentioning
confidence: 99%
“…Monocots do not exhibit secondary thickening and ray cells thus the osmoticum and sucrose transport theory do not apply to monocots (Andre, 1998). Selection for root pressure in these species solves the embolism repair problem and negates the need for carbohydrate transport along the pathway common in woody angiosperms (Brodersen et al, 2013). However, Stiller et al (2005) showed the presence of "novel" refilling in rice in presence of high negative pressure and suggested that in upland or low-rainfed rice this mechanism can serve side by side of a positive root pressure.…”
Section: Genetic Control Of Refilling Mechanismmentioning
confidence: 99%